All my thanks and love to quilts : art quilts created by Keiko Goke - Gōke, Keiko (Design Originals, an imprint of Fox Chapel Publishing, 2012)
"Keiko Goke is a world renowned quilter and fabric designer. This book chronicles 70 original quilts. There are eight themes of collections such as traditional, applique, alphabet, heart, circle, log cabin, Japanese fabric and the author's favorite. There also are step-by-step instructions for design and piecing with illustrations and photos"--